A Study of the Dominant Type of Technique (Controlled, Semicontrolled and Free) of Two English Teachers from a Languages Teaching Program Estudio acerca del tipo de técnica dominante (controlada, semicontrolada y libre) de dos profesores de inglés de un programa en licenciatura en idiomas - Francia del Pilar Gavilán Galindo (Universidad Nacional de Colombia, 2008)
This article shows the process and emerging results from a study held at a private university in Bogotá, Colombia. It aims at describing and interpreting the dominant kind of language teaching technique: controlled, semicontrolled and free (Brown, 2001) within the context of two first semester English teachers of a languages teaching program. Data collection was based upon class observations, teachers' logs and a semi-structured interview that permitted triangulation of information in order to figure out the central research query. The analysis showed that the controlled technique predominates in both teachers' classes. Thus, this study intends to foster reflection and pedagogical debate regarding its implications for ELT instruction within that university. Este artículo describe el proceso y resultados de un estudio realizado en una universidad privada en Bogotá, Colombia. Busca describir e interpretar el tipo dominante de técnica en la enseñanza de una lengua extranjera: controlada, semicontrolada y libre (Brown, 2001), en el contexto de las clases de inglés de dos profesores de primer semestre de un programa de licenciatura en lenguas extranjeras. La recolección de información se basó en observaciones, fichas de clase y una entrevista semiestructurada, las cuales permitieron triangular los datos con el objetivo de resolver la principal pregunta de investigación. El análisis de la información indicó que la técnica controlada predomina en las clases de ambos profesores. Por tanto, este estudio busca promover la reflexión y debate pedagógico sobre las implicaciones de dicha técnica en la enseñanza del inglés como lengua extranjera en esa institución.